1981
DOI: 10.1007/bf00918178
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a “friendly visitor” program on the cognitive functioning and morale of elderly persons

Abstract: Forty-nine nursing home residents were randomly assigned to a visitation condition focusing on conversational interaction, a visitation condition in which the playing of cognitively challenging games supplemented conversation, or a no-treatment control condition. Each subject in a visitation condition was visited by an undergraduate student twice per week for 8 weeks. Before and after the visitation period, all subjects were given four tests of cognitive functioning (vocabulary, matrices, memory, problem-solvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Several participants also described the memoirs as a catalyst to organize their personal effects to pass along to Downloaded by [The University of Manchester Library] at 13:54 02 November 2014 their relatives. When the older adult is in poor health (i.e., frail, cognitively impaired, homebound, nursing home resident), the service provided may be friendly visiting (e.g., Reinke et al, 1981), companionship (e.g., Greene, 1998), or completion of household tasks or chores (Bullock & Osborne, 1999)-services that are also valuable to the older adult participant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several participants also described the memoirs as a catalyst to organize their personal effects to pass along to Downloaded by [The University of Manchester Library] at 13:54 02 November 2014 their relatives. When the older adult is in poor health (i.e., frail, cognitively impaired, homebound, nursing home resident), the service provided may be friendly visiting (e.g., Reinke et al, 1981), companionship (e.g., Greene, 1998), or completion of household tasks or chores (Bullock & Osborne, 1999)-services that are also valuable to the older adult participant.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies used a focus group methodology to inquire about the older adult experience; this method was selected for use in the current study. Researchers also evaluated other outcomes for older adults including well-being (Yuen, Huang, Burik, & Smith, 2008), generativity (Herrmann et al, 2005), positive behaviors (Newman & Ward, 1993), and moral and cognitive function (Reinke, Holmes, & Denney, 1981).…”
Section: Intergenerational Programsmentioning
confidence: 99%
“…Low scores were observed after stroke (Löfgren et al, 1999), hip fracture (Shepherd and Prescott, 1996), and in those with poor nutritional status (Balcombe et al, 2001). Good morale has been shown to be correlated with perception of situational control (Ryden, 1984) and inversely correlated with death anxiety (Given and Range, 1990), while a 'friendly visitor' program had been shown to improve morale in a nursing home (Reinke et al, 1981). The close relationship between PGMS and GDS has also been observed (Löfgren et al, 1999;Shepherd and Prescott, 1996;Coleman et al, 1995).…”
Section: Quality Of Life In Elderly Chinesementioning
confidence: 93%
“…To this end, hospital-based and home-based visitor programs where kindness is provided by volunteers unknown to the recipient are popular, and studies have reported a wealth of related benefits such as lower medication use, increased happiness and vigor, and increased cognitive functioning (Reinke, Holmes, & Denney, 1981;Schulz, 1976;Wheeler et al, 1998). Also unique to PIF is the possibility that individuals can help someone else in return, potentially ameliorating the negative effects described above.…”
mentioning
confidence: 99%